Association between dietary vitamin C intake and gout among American adults - Zou, Yadan; Liu, Yongyu; Li, Shengguang (Frontiers in Immunology, 2024)
Gout is a common type of inflammatory arthritis. Vitamin C is a potent antioxidant that neutralizes reactive oxygen species. However, the association between dietary vitamin C levels and gout remains unclear. This study evaluated the relationship between dietary vitamin C intake and gout. Methods: Cross-sectional data from individuals aged > 20 years who participated in the National Health and Nutrition Examination Survey between 2013 and 2018 were collected. Details on gout, dietary vitamin C intake, and several other essential variables were recorded. Results: There were 12589 participants, 5% (652/12589) of whom experienced gout. Compared with individuals with lower vitamin C consumption in the Q1 group (≤19.9 mg/day), the adjusted odds ratio(OR)values for dietary vitamin C intake and gout in the Q2 group (19.9-49.7 mg/day), Q3 group (49.7-110.375 mg/day), and Q4 group (≥110.375 mg/day) were 0.87 (95% confidence interval (CI): 0.69-1.1, P = 0.237), 0.81 (95% CI: 0.64-1.02, P = 0.076), and 0.77 (95% CI: 0.6-0.99, P= 0.042), respectively. Accordingly, the association between dietary vitamin C intake and gout exhibited an Lshaped curve (nonlinear, P = 0.245) in a restricted cubic spline. Subgroup analysis revealed significant interactions between vitamin C levels and gout according to sex (P < 0.05). When we used data on dietary vitamin C from the second survey, we observed a similar inverse association between vitamin C intake and gout. The vitamin C was also negatively associated with hyperuricemia (OR, 0.94; 95% CI, 0.9-0.98, P=0.005). Compared with Q1, the adjusted OR values for dietary vitamin C and hyperuricemia in Q2, Q3, and Q4 were 0.77 (95% CI: 0.69-0.86, P = 0.65), 0.81 (95% CI: 0.72-0.91, P = 0.014), and 0.72 (95% CI: 0.64-0.81, P < 0.001), respectively. No association was observed between vitamin C supplementation and gout. Conclusion: The population-based data indicate that dietary vitamin C intake is inversely associated with gout. These findings support the potential role of vitamin C in preventing gout.